2011
DOI: 10.5101/nbe.v3i4.p243-248
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Gold Nanoparticles Inside Carbon Nanotubes by Oligonucleotides

Abstract: Delivery of gold nanoparticles with 2 nm or so in diameter inside multiwall carbon nanotubes (MCNTs) by oligonucleotides was performed under the condition of 400 k and 3 bar for 20 min. The Au-oligo-CNT complexes were first purified via 1% agarose gel electrophoresis and then analyzed via high resolution transmission electron microscopy (HR-TEM) and energy dispersive X-ray spectroscopy (EDX). The results showed that the excess of oligonucleotides, Au nanopartilces and the Au-oligo hybrids attached to the outsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…For example, carbon nanotubes have been used as delivery system for gene therapy [4], also used for biosensor for ultrasensitive detection of biomarkers [5], more important, carbon nanotubes can be used for near infrared imaging and photothermal therapy [6]. In our previous work, we also confirmed that carbon nanotubes can be filled with DNA or peptide molecules [7,8], can take antisense oligonucleotides into HL-60 cells and inhibited tumor cell growth [9], highly suggesting that carbon nanotubes may be good delivery system and have highly potential in gene or drug storage and delivery system in molecular therapy of diseases.…”
Section: Introductionsupporting
confidence: 51%
“…For example, carbon nanotubes have been used as delivery system for gene therapy [4], also used for biosensor for ultrasensitive detection of biomarkers [5], more important, carbon nanotubes can be used for near infrared imaging and photothermal therapy [6]. In our previous work, we also confirmed that carbon nanotubes can be filled with DNA or peptide molecules [7,8], can take antisense oligonucleotides into HL-60 cells and inhibited tumor cell growth [9], highly suggesting that carbon nanotubes may be good delivery system and have highly potential in gene or drug storage and delivery system in molecular therapy of diseases.…”
Section: Introductionsupporting
confidence: 51%
“…In addition, gold nanoparticles (GNPs) have been of great interest because of their high extinction coefficient and a broad absorption spectrum in a visible light that is overlapped with the emission wavelength of usual energy donors [18][19][20][21]. As a photoluminescence (PL) quencher of organic dyes, GNPs were employed to detect single-mismatched nucleotides based on a molecular beacon technique and other protein interactions [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, QDs have been favorably adopted in the FRET-based studies due to their distinct optical characteristics [17]. In addition, gold nanoparticles (GNPs) have been of great interest because of their high extinction coefficient and a broad absorption spectrum in a visible light that is overlapped with the emission wavelength of usual energy donors [18][19][20][21]. As a photoluminescence (PL) quencher of organic dyes, GNPs were employed to detect single-mismatched nucleotides based on a molecular beacon technique and other protein interactions [17].…”
Section: Introductionmentioning
confidence: 99%